A Review of Topological Semimetal Phases in Photonic Artificial Microstructures - Boyang Xie (Frontiers Media S.A., 2021)
In the past few years, the concept of topological matter has inspired considerable research in broad areas of physics. In particular, photonic artificial microstructures like photonic crystals and metamaterials provide a unique platform to investigate topologically non-trivial physics in spin-1 electromagnetic fields. Three-dimensional (3D) topological semimetal band structures, which carry non-trivial topological charges, are fundamental to 3D topological physics. Here, we review recent progress in understanding 3D photonic topological semimetal phases and various approaches for realizing them, especially with photonic crystals or metamaterials. We review topological gapless band structures and topological surface states aroused from the non-trivial bulk topology. Weyl points, 3D Dirac points, nodal lines, and nodal surfaces of different types are discussed. We also demonstrate their application in coupling spin-polarized electromagnetic waves, anomalous reflection, vortex beams generation, bulk transport, and non-Hermitian effects.